EVALUATION OF SEMINAL PLASMA TAC IN RELEVANCE TO SERUM DHEA, TESTOSTERONE LEVELS AS A DIAGNOSTIC VALUE IN INFERTILE MEN: Life Science-Medicine - DHAMIN. OLEIWI, FAHAD; A. L. MOSSA, HAYDER; O. SELMAN, MOHAMMAD (International Journal of Life Science and Pharma Research, 2019)
Oxidative stress (OS) plays a vital role in human reproduction. It rises as a consequence of excessive reactive oxygen species (ROS) production and/or reduced total antioxidant capacity (TAC) protection. Oxidative stress mediated damages to the plasma membrane of the spermatozoa may account for defective spermatozoa function parameters that are observed in a high percentage of infertile patients. This study is aimed to evaluate the relationship between level of seminal plasma TAC in relevance to serum dehydroepiandrosterone (DHEA) and testosterone in serum with the assessment of routine spermatozoa parameters in different groups of infertile men. Blood and semen samples were collected from the infertile and fertile subjects. The total numbers of samples were 80, the infertile men were divided into three groups (azoospermic, oligozoospermic and asthenozoospermic) each with 20 samples, and 20 fertile men. Then the levels of serum hormones and seminal plasma TAC were measured using Enzyme Linked Immunosorbent Assay (ELISA). The results of hormonal levels in serum showed that there were no significant differences (p>0.05) in the level of DHEA between control group and infertile groups, even though the level of DHEA were in the lower limit of normal among azoospermic group. There was no significant difference (p>0.05) in the level of testosterone among study groups but it was in the lower limit among azoospermic men. This study is reveals that there was a highly significant (p<0.001) difference in the level of TAC between study groups and control group which was increased among normozoospermic men and decreased among infertile groups. The lower limit of TAC was seen in asthenozoospermic men. The results of this study also showed that there were a relationship between TAC of seminal plasma and hormonal levels, and that TAC are positively correlated with testosterone and DHEA. From the results obtained it could be concluded that; DHEA and testosterone have an effect on male fertility via regulation of seminal plasma TAC. On the other hand seminal plasma TAC are negatively correlated with the number of immotile spermatozoa and positively correlated with concentration, progressively motile and morphologically normal spermatozoa.